Komunikasi Publik Pemerintah Kota Medan Dalam Pengalihan Kewenangan Kebijakan Terkait UU No. 23 Tahun 2014 - Rahmansyah F A I K Rambe; Ritonga, Aulia Rahma; Dalimunthe, Maulana Andinata (Talenta Publisher, 2023)
The purposes of this study to see how the implementation of public communication management carried out by the City Government of Medan (Pemko Medan), regarding the transfer of secondary education authority based on Law no. 23 of 2014. To see this problem, we will look at the implementation and factors that influence the management of public communication, namely the medium of communication, resources, facilities and infrastructure, disposition and structure of the bureaucracy. To analyze this problem, researchers used a qualitative methodology with descriptive methods. Data collection was carried out by means of observation, in-depth interviews, and literature studies. The results of this study show that the public communication carried out by Pemko Medan has been going quite well. Pemko Medan is able to socialize the policies and programs they have to schools, teachers, and the community. This public communication activity is carried out by optimizing the facilities and infrastructure that they have, such as providing scholarships to students and the existence of clear and targeted incentives for the human resources (HR) they have, namely teachers. In addition, Pemko Medan has also carried out effective public communication with the Provincial Government of North Sumatra (Pemprovsu) so that the transfer of authority that takes place between Pemko Medan and Pemprovsu can run well.